Physiological and morphological changes of heat stress in «Astana» variety of wheat plants: the role of relative water content - Talgatbekova , D.; Samat , A.; Tekebayeva , Zh.; Amantayeva , A.; Masalimov , Zh.; Temirkhanov , Zh.; Nurbekova , Zh. (Eurasian Journal of Applied Biotechnology, 2026)
Wheat (Triticum aestivum L.) is one of the most widely consumed cereal crops in the world. High temperature is one of the important abiotic stresses affecting plant growth because global warming is one of the major problems in the world today. Physiological and biochemical changes occurring in cells under abiotic stress conditions slow down plant growth and development, which ultimately leads to a decrease in wheat yield. The aim of the research was study how heat stress affects wheat growth and to find out the changes in wheat plants shape and functions under high temperature. In this study wheat of the Astana variety was used and a comparison was made between the control plants grown at 25°C and the stressed plants grown at 40°C. As a result of the work morphological and physiological changes were observed. We studied the average length of wheat roots and shoots and relative water content of Astana variety of wheat plants. In stress group roots and shoots of wheat plants were reduced in size compared to control plants and the relative water content of plants grown at optimal temperature was higher compared to plants grown under heat stress.